Distance travelled to tertiary pediatric care impacts care-seeking behavior and hospital outcome in Vietnam - David A Rollins; Timothy T Xu; Viet Hoang; Khang Tuan Hoang; Sarah S Kang; Toan Ngoc Pham; Duy Ngoc Le; Yves Ouellette (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background The absence of appropriate and timely critical care in resource-limited countries like Vietnam contributes to poor outcomes and excessive mortality in the acutely ill, pediatric population. Often, tertiary care is limited to major urban centers and patients from remote locations face lengthy travel. How these distances impact care-seeking behavior of the patients' caregiver, patient acuity on admission, and hospitalization outcome in critically ill children remains unknown. # Methods We assessed 471 pediatric patients admitted to intensive care units (ICUs) from the emergency department in a pediatric referral center in Hanoi that serves northern Vietnam. Demographic information from caregivers and medical information was collected by trained staff on site and from the medical record. Patient outcome was followed for sixty days in the ICUs. We analyzed associations between patient admission acuity and outcome to socio-geographic and-demographic data using bivariate logistic regression and log-rank analyses. # Results The median child's age in our study was 1.8 months, with the majority under 1 year (83.3%). On admission to the ICU, 40.5% of patients required life-saving treatment. Within sixty days of admission, 73.3% of patients were discharged, 21.8% experienced extended admission and 3.08% expired in the ICU. Patient and caretaker's distance from home residence to Vietnam National Children's Hospital (VNCH) greater than 60 kilometers was significantly associated with a more severe patient acuity on ICU admission (Odds Ratio, OR=2.01, 95% Confidence Limit, CL=1.33, 3.06), an extended admission or expiration in the ICU (OR=1.94, 95% CL=1.15, 3.20), a lower family income (OR=3.74, 95% CL=2.46, 5.64), lack of caregiver college education (OR=3.73, 95% CL=2.34, 6.05), and greater referrals and days delayed seeking care. # Conclusions These findings highlight numerous barriers facing acutely ill children and their caretakers, who must travel long distances to reach appropriate critical care at a tertiary referral hospital. Research into current protocols, skills, and staffing at lower facilities and public health education in these regions is needed to determine the best avenues for improvement of critical care services beyond tertiary centers.